Case Report: A Case of Epstein-Barr Virus-Associated Acute Liver Failure Requiring Hematopoietic Cell Transplantation After Emergent Liver Transplantation - Nakajima, Koji; Hiejima, Eitaro; Nihira, Hiroshi; Kato, Kentaro; Honda, Yoshitaka; Izawa, Kazushi; Kawabata, Naoko; Kato, Itaru; Ogawa, Eri; Sonoda, Mari; Okamoto, Tatsuya; Okajima, Hideaki; et al. (Frontiers in Immunology, 2022)
Hepatic manifestations of Epstein-Barr virus (EBV) infection are relatively common, mild, and self-limiting. Although fulminant hepatic failure has been reported in a few cases, the contributing factors are unclear. This report discusses a pediatric case of EBV-associated acute liver failure that required urgent liver transplantation; however, liver damage continued to progress post-liver replacement. Monoclonal CD8+ T cells that preferentially infiltrated the native and transplanted liver were positive for EBV-encoded small RNA, suggesting a pathophysiology similar to that of EBV-associated hemophagocytic lymphohistiocytosis and chronic active EBV infection. Therefore, subsequent chemotherapy and hematopoietic cell transplantation was conducted, which led to cure. This is the first case of EBV-associated acute liver failure that relapsed post-liver transplant. As such, it sheds light on an under-recognized clinical entity: liver-restricted hyperinflammation caused by EBV-infected monoclonal CD8+ T cells. This phenomenon needs to be recognized and differentiated from hepatitis/hepatic failure caused by EBV-infected B cells, which has a relatively benign clinical course.